2018
DOI: 10.3762/bjnano.9.279
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic force microscopy for the accurate characterization of interphases in nanocomposites

Abstract: The unusual properties of nanocomposites are commonly explained by the structure of their interphase. Therefore, these nanoscale interphase regions need to be precisely characterized; however, the existing high resolution experimental methods have not been reliably adapted to this purpose. Electrostatic force microscopy (EFM) represents a promising technique to fulfill this objective, although no complete and accurate interphase study has been published to date and EFM signal interpretation is not straightforw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…The topography and frequency shift Δ f (used to calculate the force gradient) signal of the detection are shown in Figure b–e, and Figure e is the average profile of the signal shown in Figure b,c. It can be seen clearly that the signal difference generated by the 50-nm-thick, totally different interface is equivalent to the error in the test . The results in that study imply that even a great change of interface polarization has a very weak impact on the electrostatic force measured by EFM.…”
Section: Interface Study By Scanning Probe Microscopy-based Measurementmentioning
confidence: 68%
See 2 more Smart Citations
“…The topography and frequency shift Δ f (used to calculate the force gradient) signal of the detection are shown in Figure b–e, and Figure e is the average profile of the signal shown in Figure b,c. It can be seen clearly that the signal difference generated by the 50-nm-thick, totally different interface is equivalent to the error in the test . The results in that study imply that even a great change of interface polarization has a very weak impact on the electrostatic force measured by EFM.…”
Section: Interface Study By Scanning Probe Microscopy-based Measurementmentioning
confidence: 68%
“…It can be seen clearly that the signal difference generated by the 50-nm-thick, totally different interface is equivalent to the error in the test. 211 The results in that study imply that even a great change of interface polarization has a very weak impact on the electrostatic force measured by EFM. Recently, in the topic of interface detection by EFM, the influence of the morphology, polarization, and charge in the interfacial region on measurement was analyzed by FEM simulation (Figure 13f).…”
Section: Spatial Resolution In the Detection Of Electrostaticmentioning
confidence: 74%
See 1 more Smart Citation
“…Because a precise value for tip size is essential for quantifying electrostatic force gradients, we independently calibrated the tip. Two fitting parameters are generally used to model a tip: the tip apex radius, R apex , and the half an gle of the cone, θ, and there are several potential approaches. , Similar to Fumagalli et al, the capacitive force gradient was measured at various lift heights, z , for a gold-coated steel substrate. The results were fitted to the analytical equation: C m e t a l ( z ) = 2 π ϵ o R a p e x ln ( 1 + R a p e x z false( 1 sin .25em θ false) ) Based on that fitting, we calculated θ = 12° and R apex = 29 nm, which correspond well with the manufacturer’s claim of a 25 nm tip radius and side angle of 12°.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, DSC and NMR studies revealed that local permittivity is linked to interphase, and TiO 2 nanoparticles inhibit local chain segment mobility. Khoury et al [ 137,138 ] investigated interphase using EFM and DC or AC gradient detection. The main goal of this work was to create an experimental protocol for analyzing and calibrating EFM signals for use in interphase studies.…”
Section: Dielectric Interfacesmentioning
confidence: 99%